Play framework essentials : an intuitive guide to creating easy-to-build scalable web applications using the Play framework - Richard-Foy, Julien (Community experience distilled., 2014)
Chapter 2: Persisting Data and Testing; Testing your web service; Writing and running tests; Testing the HTTP layer; Using the reverse router to generate URLs; Running a fake Play application; Effectively writing HTTP tests; Persisting data; Using a relational database; Getting a reference to the currently running application; Using a database management library; Using Slick in Scala; Using JPA in Java; Integrating with other persistence technologies; Populating the database with fixtures; The application''s Global object; Managing database schema evolutions.